Efeitos de um programa de autocuidados sobre a síndrome de Burnout em professores do ensino fundamental - Soares, Caroline Fernanda (2025)
Burnout Syndrome is an occupational problem among teachers, related to continuous stressors that result in exhaustion. Self-care practices, such as breathing and relaxation, are effective interventions for stress prevention and reduction. Concurrently, the Programming of Conditions for Behavior Development (PCDC) is an efficient technology for teaching specific behaviors. The present study aimed to evaluate the contribution of applying a PCDC-based teaching program of relaxation and emotional self-control strategies to reduce the risks of Burnout Syndrome in teachers. Six elementary school teachers from a São Carlos State Public School participated, divided into an experimental group (n=3) and a control group (n=3). The pre-test included the Brazilian Burnout Scale (EBBurn), the WHOQOL-bref, the LIPP Stress Symptoms Inventory for Adults - Revised (ISSL-R), and a Self-Care Behaviors Questionnaire. The intervention, applied to the experimental group, was a 9-weekly session program, based on PCDC and Behavioral Skills Training (BST), covering relaxation techniques and other self-care practices. Post-test and follow-up (two months after the post-test) consisted of reapplying the same instruments. Results for the experimental group revealed significant reductions in mean Stress levels (69.9% decrease post-test and 51.8% at follow-up) and Burnout levels (23.7% decrease post-test and 22.2% at follow-up). Mean quality of life for this group increased (31% post-test and 27.5% at follow-up). The control group, in contrast, maintained stable levels across all instruments. Additionally, self-care behaviors in the experimental group showed a notable increase (86.6% post-test, with maintenance at follow-up), and the perception of positive consequences, like stress reduction, reinforced adherence. Findings support self-care studies in stress reduction and the effectiveness of PCDC-based programs for preventing and managing Burnout Syndrome in teachers.